Development of power-operated continuous-feed green-pea sheller - SELVAN, M MUTHAMIL; MANI, INDRA (The Indian Journal of Agricultural Sciences, 2020)
Shelling of green-peas from pods is still a manual operation among vegetable vendors in India making shelling operation a crucial and time consuming task. There was a need for a machine that would accept a variety of green-pea pods as input and produce green-peas as output, with a little to no work required by the operator. Therefore, a machine was specially designed, fabricated, and tested to master shelling management in 2018 in New Delhi. It was a vertical free-standing unit and consisted of electric motor, feeding tray, two shelling rollers, and outlet-tank. The capacity of the machine was 106.8±6.3 kg/h by engaging single labourer and the cost of operation ₹ `9/h while cost of machine was `₹ 30,000 as on April 2018. Shelling efficiency was found to be 97.5±1.9% with negligible mechanical damage and the physical parameters of machine-shelled peas were at par with manually-shelled ones. Shelling through machine gave 79.4% cost-saving, and 99.8% time-saving and break-even point for utility of this machine was 30 t/annum while pay-back period was 1.4 year. The capacity, ergonomics, and performance of the machine met the standards. The machine was recommended for small farm holders and vegetable vendors around the nation since the machine can provide efficient shelling of grean-peas commercially.